Knowing, as long as it asks about things. - Fúnez, Rubén (Teoría y Praxis, 2022)
This article presents three ideas. First, a reflection on knowing through the history of philosophy. Second, the logic of reality as a way to access the problem of knowing. Finally, the importance that sensibility begins to acquire, in the apprehension of the actual state of things.